Analisis Pengaruh Faktor Non-Ekonomi terhadap Sikap Pedagang Madura dalam Membayar Zakat Perdagangan - Nely Novia; Iswan Noor; Marlina Ekawaty (AL-MUZARA'AH, 2018)
Zakah maal is one of the kind of zakat that must be paid by muslims who work as traders and have the treasures that reach nisab, haul, and also fulfill other conditions. The purpose of this research is to know the influence of non-economic factors namely knowledge of zakah on trade (X1), work environment (X2), religiosity (X3), and education (X4) on the attitudes of Madurese traders in Malang in paying zakah on trade (Y). The method used in this study is multinomial logit analysis. The results of this study indicate that simultaneously the knowledge (X1), work environment (X2), religiosity (X3), and education (X4) significantly influence the attitude of Madurese traders in paying zakah on trade (Y). Further partially, Madurese traders' attitude in paying zakah on trade (Y) is influenced by knowledge (X1), work environment (X2), religiosity (X3), and education (X4).